Efforts to Improve the Ability to Understand the Extent of Trapezium and Kites in Mathematics for Class V Students at SD Negeri I Dadahup Academic Year 2017/2018 - Nyaing (JURNAL PENDIDIKAN, 2020)
This research is based on the following problems: a) Does the Novick Model Learning affect Mathematics learning outcomes? b) How high is the level of mastery of Mathematics subject matter with the application of the Novick Model Learning method? The objectives of this study were: a) To reveal the effect of Novick's Model Learning on Mathematics learning outcomes. b) Want to know how far the understanding and mastery of Mathematics subjects after the implementation of the Novick Model Learning model. This research uses action research as many as three rounds. Each cycle consists of four stages, namely: design, activity and observation, reflection, and revision. The target of this research is the Class V students. The data obtained are in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysis, it was found that student learning achievement had increased from cycle I to cycle III, namely, cycle I (63%), cycle II (86%), cycle III (95%). The conclusion of this study is that the Novick Model cooperative method can have a positive effect on the learning motivation of Class V SDN Semangat Dalam 1 students, and this learning model can be used as an alternative to mathematics.